Study on Chemical Constituentsfrom the Roots of Panax bipinnatifidius Seem. Collected in Sapa, Laocai - Hao, Do Van; Hue, Nguyen Thi; Thuy, Nguyen Thi Thu; Ngan, Dang Thi; Bich, Dao Thi Hong; Anh, Nguyen Thi Hoang; Huong, Duong Thi Ly; Tung, Nguyen Huu (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 33 No 2, 2017)
Panax bipinnatifidius Seem. is one of the highly valuable and most used in Vietnam. By using the chromatographic techniques, we have purified three compounds from the ethyl acetate fraction of the root of P.bipinnatifidius Seem.Three compounds were identified as β -sitosterol ( 1 ), oleanolic acid ( 2 ), and daucosterol ( 3 ), respectively, on the basis of analysis of NMR and MR spectrum data. This is the first publication on the isolation of these compounds from P. bipinnatifidius Seem. in Vietnam. nnatifidius Seem. in Vietnam